2021
DOI: 10.1088/1361-6528/abe153
|View full text |Cite
|
Sign up to set email alerts
|

3D MXene microspheres with honeycomb architecture for tumor photothermal/photodynamic/chemo combination therapy

Abstract: The MXene combining high surface area, prominent biocompatibility, and wide near infrared (NIR) absorption has been recognized as one of the most promising materials for tumor therapy. The application of MXene in tumor therapy is negatively affected by the current design methods lack the control of size distribution and the great tendency to agglomerate as well as poor photodynamic therapy. To solve the above problems, we report a facile strategy to process Ti3C2 nanosheets into three-dimensional (3D) structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The (002) and (110) peaks of MQD and the (101) and ( 200) peaks of the titanium dioxide (TiO2) (JCPDS Card No. 71-1168) can be presented in the curve of the MQD sample, which indicated that a part of MQD was oxidized to TiO2 [46]. Moreover, the peaks of After that, the zeta potentials of nanomaterials were tested.…”
Section: Samples Characterizationmentioning
confidence: 95%
“…The (002) and (110) peaks of MQD and the (101) and ( 200) peaks of the titanium dioxide (TiO2) (JCPDS Card No. 71-1168) can be presented in the curve of the MQD sample, which indicated that a part of MQD was oxidized to TiO2 [46]. Moreover, the peaks of After that, the zeta potentials of nanomaterials were tested.…”
Section: Samples Characterizationmentioning
confidence: 95%
“…[114] Reproduced with permission from ref. [114] Copyright 2021 IOP Publishing. (l) Stability test for the photothermal conversion performance of MXenes.…”
Section: Materials/structuresmentioning
confidence: 99%
“…(l) Stability test for the photothermal conversion performance of MXenes. [114] Reproduced with permission from ref. [114] Copyright 2021 IOP Publishing.…”
Section: Materials/structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…2 More attractively, it can effectively transform light to heat when triggered by NIR irradiation, 15 hence becoming an outstanding photosensitizer to treat cancer based on photothermal therapy (PTT), which has nowadays been recognized as an effective biomedical tool to combat cancers due to its remote controllability, easy applicability, and minimal toxicity. [16][17][18] And when PTT was used in combination with chemotherapy, it was found more efficient in tumor suppression compared with either treatment alone. 14 Stimuli-responsive PNIPAM hydrogels introduced into GO have been studied extensively, [19][20][21] but developing a new PNIPAM@GO core-shell microsphere combined chemotherapy and NIR triggered PTT is still a challenge.…”
Section: Introductionmentioning
confidence: 99%